(untitled) (Journal of Computational Mathematics, 1990)
This paper presents a method of finding a strictly feasible solution for linear constraints. We prove, under certain assumption, that the method is convergent in a finite number of iterations, and give the sufficient and necessary conditions for the infeasibility of the problem. Actually, it can be considered as a constructive proof for the Farkas lemma.